2016
DOI: 10.1117/12.2214546
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low NA Yb doped preforms (<0.03) fabricated by MCVD

Abstract: We report the fabrication of extremely low NA preforms (<0.03), highly doped with Yb using a conventional Modified Chemical Vapor Deposition (MCVD) system. Our lowest NA preform (0.025 NA) was drawn to a 52um core step-index double-clad fiber operating in a single mode regime (M 2 =1.04). The fiber had a mode field diameter (MFD) and an effective area (Aeff) greater than 35um and 1000um 2 respectively. In a fiber laser configuration, the efficiency was greater than 85% without any sign of photodarkening. To th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Vincent et al reported a 1.6 kW nearly diffractionlimited output generated in an ultra-low-NA SIF with a 52 µm core diameter and a core NA of 0.025 [53] . Besides, a 3 kW laser output without PD and MI was achieved based on a low-NA fiber with a core diameter of 35 µm [54] . Very recently, Beier et al presented a narrow linewidth singlemode fiber amplifier system up to 4.4 kW with single-mode beam quality achieved by lowering the NA of the fiber to ∼0.04 [55] .…”
Section: Single-mode Operationmentioning
confidence: 99%
“…Vincent et al reported a 1.6 kW nearly diffractionlimited output generated in an ultra-low-NA SIF with a 52 µm core diameter and a core NA of 0.025 [53] . Besides, a 3 kW laser output without PD and MI was achieved based on a low-NA fiber with a core diameter of 35 µm [54] . Very recently, Beier et al presented a narrow linewidth singlemode fiber amplifier system up to 4.4 kW with single-mode beam quality achieved by lowering the NA of the fiber to ∼0.04 [55] .…”
Section: Single-mode Operationmentioning
confidence: 99%
“…Transmission loss (dB/m) = 10 ∆L log 10 P short /P long (1) where P short and P long are the detected transmitted power through the fiber before and after the fiber is cut respectively, and ∆L is the length of the cut piece. The average transmission loss for each fiber was then obtained by linearly fitting the five measurement points and calculating its slope.…”
Section: Transmission Lossesmentioning
confidence: 99%
“…Optical fibers doped with ytterbium (Yb) ions have attracted increasing interest for the development of high-power laser systems for applications requiring bright and high power beams, such as materials processing, medicine and telecommunications [1][2][3][4][5][6]. In comparison with other rare-earth (RE) ions, Yb is the favored lasing ion for emission at around 1 µm due to its numerous advantages, such as a simple energy-level diagram with only two electronic multiplets ( 2 F 5/2 and 2 F 7/2 ), a long fluorescence lifetime which provides the benefit of energy storage, and broad absorption and emission bands [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative technology is using gas-phase doping in MCVD system, where large-size Yb 3+ -doped silica core with high homogeneity has been achieved. Petit et al [11] have successfully prepared an Yb 3+ /Al 3+ /F --co-doped silica preform for double-clad fibers using a proprietary rare-earth vapor delivery system coupled to a standard MCVD lathe and achieved a low numerical aperture (NA) of 0.025 ± 0.005. M. E. Likhachev et al [12][13][14] developed an Yb 3+ /Al 3+ /P 5+ -co-doped active tapered cladding fiber with a core diameter of 67 um and core flatness was good to get perfect Gaussian mode shape with M 2 < 1.15.…”
Section: Introductionmentioning
confidence: 99%